The price of valor [large type] - Warren, Susan May, 1966- (Warren, Susan May, 1966- Global search and rescue, 2021)
"Former Navy SEAL Hamilton Jones thought the love of his life was dead. But when he hears she might still be alive, he will stop at nothing to find her and bring her home. When he discovers her reason for staying away, he must choose between her and the nation he vowed to protect"--